Thermal and mechanical properties of magnesium AZ91D/Aramid pulp composites. (2022) - Balamurugan, A.; Chithra Devi, R.; Suresh, K.C.; Bhuvaneswari, M.
Abstract: Composites made from aramid pulps and magnesium AZ91D were created under ambient pressure drying to maintain the integrity and improve the mechanical characteristics of fiber/magnesium AZ91D composites without sacrificing thermal insulation qualities. To keep the integrity and adhesion of magnesium AZ91D matrix, the large fibrillated fibres of aramid pulps are plated in the magnesium AZ91D matrix. Compressive strength raised noticeably up to 1.2 MPa as the aramid pulp percentage increased, and the low thermal conductivity increased linearly from 0.0232 to 0.0278 W -1 m −1 K. The thermostability of the composites after preparation was roughly 260 °C, according to TG-DTA (Thermogravimetry/Differential Thermal Analysis), which was mostly in need of thermal stability of pure magnesium AZ91D. Aramid pulps can be used as reinforcements to produce superior magnesium AZ91D composite materials with integral microstructures, enhanced mechanical strength, and customized thermal characteristics.